Pengetahuan, Sikap, dan Pelanggaran Hukum Tort di Antara Kepala Sekolah Menengah Umum Terhadap Siswa di Negara Bagian Osun, Nigeria - Timothy Olugbenga Ajadi; Musibau A. Lateef (Journal of Education and Teaching (JET), 2023)
One of the challenges in secondary schools today is infringements on students’ rights, in a tortious way that may also constitute breach of the Child’s Right Act of 2003 in Nigeria.  These breach on rights usually come through the administration of corporal punishments on students, and mainly because the school heads see themselves as loco parentis of the students who can, therefore, enforce any form of punishment on them in the school. This study investigated knowledge, attitude, and infringement of tort law among public secondary school heads on students in Osun State.  All the students in Osun State public secondary schools and 723 heads constituted the population.  A sample of 54 school heads and 180 students were selected using multi-stage sampling procedure.  Two instruments were designed to elicit responses from the respondents.  Descriptive and inferential statistics were used to answer the research questions raised for the study.  The results showed that school heads do not have adequate knowledge of tort law and that both the school heads and students have poor attitude toward it tort law.  The study recommends that short term training on student’s right, how they can be legally protected and tort law be organised for school heads.